Characteristics and Performance of Hens from Red Jungle Fowl Offspring in the Community in Bengkulu City: Karakteristik dan Performa Induk Ayam Keturunan Ayam Hutan Merah Pada Masyarakat di Kota Bengkulu - Sutriyono, Sutriyono; Santoso, Urip; Brata, Bieng; Suherman, Dadang (Buletin Peternakan Tropis, 2024)
Red Junglefowl (RJF) is a germplasm in Bengkulu, living in forests and plantations, and its population is estimated to continue to decline. Domestication has been carried out by the community, and there has been crossbreeding with local chickens and producing offspring. The study was conducted for 4 months in Bengkulu City to identify rearing management of hen, characteristics of hen, production characteristics, and to develop development scenarios. Twenty-seven respondents were used in the study. Data were obtained through observation and interviews, and filling out questionnaires. The data collected were maintenance management of hen, population, body weight, age of first laying eggs, egg production, and egg weight. The results of the study, farmers rearing hen by caged, released, and a combination of both methods. The feed given was local feed (corn, rice, brown rice, cooked rice) and commercial feed BR 1. The maximum weight of the hen was 995.00 grams and the minimum was 600.00 grams, the average was 738.96±93.07 grams, egg production was 9.68±2.60/hen/period, egg laying period 3.42 times/year, egg weight 28.56±5.28 grams. The initial population was 90 and the final 570, the average length of raising chickens was 9.45 years, an increase of 50.77/year (56.41%). In conclusion, the development of the population of jungle fowl offspring was slow; and the values ​​of body weight, egg production, egg weight were higher than red jungle fowl and lower than native chickens. Development, genetic improvement, increasing the number of parent hens and egg hatching, and improving maintenance management.